2020
DOI: 10.19094/contextus.2020.60264
|View full text |Cite
|
Sign up to set email alerts
|

Visual merchandising: Uma análise bibliométrica e proposta de pesquisas futuras

Abstract: Este trabalho teve como objetivo investigar os estudos sobre visual merchandising em aspectos teóricos, metodológicos e empíricos. Foi realizada uma pesquisa bibliométrica a partir de 35 artigos publicados em periódicos. As análises apresentam o número de artigos por ano, principais periódicos, referências mais citadas, palavras-chave mais utilizadas, além da metodologia considerando abordagem, método de pesquisa, técnica de coleta e análise de dados. Foi possível concluir que o tema é relativamente novo justi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
0
0
Order By: Relevance
“…Also when consumers feel there is a similarity between the fashion products they purchase at fast-fashion outlets with their self-image, or how they perceive other people see them, the consumers would have the intention to recommend the outlet to their relatives in the future. (Batista et al, 2020) The analyzes carried out allowed us to conclude that the visual merchandising theme is still a relatively new field of research because although the first article identified that addresses the theme was from 1998, most of the analyzed articles were published five years ago or less. As a development field, there are few national citations, that is, few articles cited the works selected for analysis.…”
Section: Visual Merchandising and Brand Imagementioning
confidence: 99%
“…Also when consumers feel there is a similarity between the fashion products they purchase at fast-fashion outlets with their self-image, or how they perceive other people see them, the consumers would have the intention to recommend the outlet to their relatives in the future. (Batista et al, 2020) The analyzes carried out allowed us to conclude that the visual merchandising theme is still a relatively new field of research because although the first article identified that addresses the theme was from 1998, most of the analyzed articles were published five years ago or less. As a development field, there are few national citations, that is, few articles cited the works selected for analysis.…”
Section: Visual Merchandising and Brand Imagementioning
confidence: 99%